A PENGEMBANGAN PLATFORM DIGITAL HUBSPOT UNTUK MEMPERLUAS JANGKAUAN PASAR PENGRAJIN AKAR JATI DI DESA TEMPELLEMAHBANG KECAMATAN JEPON KABUPATEN BLORA - Mariyani, Anna; Nurmawati, Fulusia; Munfariqoh, Aqidatul; Rofiq, Muhammad Aunur; Mahendra, Wawan Dedi; Nafiah, Khitthatun (JURNAL SINEKTIK, 2025)
The results of interviews show that 92% of teak root craftsmen in Tempellewebang Village, Jepon District, Blora Regency have difficulty entering the international market because they have not been able to introduce themselves outside Indonesia. When marketing domestically they usually post on Instagram, marketplaces such as Shopee, Tokopedia, Blibli, etc. However, the majority of craftsmen also do not have sufficient skills in taking good photos of their products, apart from that, there are also those who are hampered by the media used when producing effective photos for online marketing materials. The advantage of the HubSpot platform as a top marketing software provider is its marketing approach. HubSpot focuses on creating content that is informative and engaging for potential clients, such as blogs, eBooks, webinars, and courses. This research is development research. The model used is the development of a 4-D model. The 4-D (Four D) development model is a learning device development model. This model was developed by Thiagarajan, S., Semmel, D. S., & Semmel (1974). The 4D development model consists of 4 main stages, namely: Define, Design, Develop and Disseminate. The samples used in this research were 100 teak root and teak furniture craftsmen in Blora Regency. The ease of using Hubspot increases the market reach of teak root and teak furniture craftsmen in Blora Regency.